1991
DOI: 10.1055/s-0038-1647477
|View full text |Cite
|
Sign up to set email alerts
|

A Synthetic Analog of Fibrinogen α27–50 Is an Inhibitor of Thrombin

Abstract: SummaryBinding of the synthetic peptide AAKDSDWPEASDEDWNYKAPSGAR, a fibrinogen α27–50 analog, to thrombin was studied by inhibition assays and affinity chromatography. Peptide α27–50 corresponds to a segment of human fibrinogen downstream from the thrombin cleavage site, with cysteine residues at positions 28, 36, 45 and 49 replaced by alanine. The peptide inhibited clotting of fibrinogen with an inhibition constant of 190–400 μM. Cleavage of fibrinopeptides A and B was inhibited by the peptide and the peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 7 publications
2
27
0
1
Order By: Relevance
“…The latter is a well-characterized nonsubstrate binding phenomenon in the interaction between human thrombin and human fibrin that is attributed to (1) residual thrombin binding at or near the substrate interaction site in the fibrin E-domain, and (2) binding at a higher-affinity binding site in the ␥Ј-variant of the fibrinogen ␥-chain. [33][34][35][36][37] The mouse ␥-chain does not contain the thrombin-binding sequence motif, 38 thus predicting the absence of a high-affinity thrombin-fibrin interaction. A preliminary analysis of binding of mouse thrombin to mouse fibrinogen failed to produce evidence for the existence of a high-affinity thrombin binding component in mouse fibrin (data not shown), consistent with the above prediction.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is a well-characterized nonsubstrate binding phenomenon in the interaction between human thrombin and human fibrin that is attributed to (1) residual thrombin binding at or near the substrate interaction site in the fibrin E-domain, and (2) binding at a higher-affinity binding site in the ␥Ј-variant of the fibrinogen ␥-chain. [33][34][35][36][37] The mouse ␥-chain does not contain the thrombin-binding sequence motif, 38 thus predicting the absence of a high-affinity thrombin-fibrin interaction. A preliminary analysis of binding of mouse thrombin to mouse fibrinogen failed to produce evidence for the existence of a high-affinity thrombin binding component in mouse fibrin (data not shown), consistent with the above prediction.…”
Section: Discussionmentioning
confidence: 99%
“…All the sites on fibrinogen A␣ that bind to thrombin are believed to be located within the first 50 residues of the A␣ chain. 30,31 Little is known, however, about the conformation of FbgA␣ in the vicinity of the R16-G17 cleavage site because many of the NMR and X-ray studies published thus far have involved the use of native thrombin and hydrolyzable peptide substrates. During these experiments, the enzyme cleaves the peptide substrate, and hence structural information is obtained only for the hydrolyzed product.…”
Section: Introductionmentioning
confidence: 99%
“…The N-terminal fragment of Aα chain is responsible for binding with thrombin and formation of fibrin polymerization sites 13. Zhang et al had expressed N-terminal truncated Aα chain in COS1 cells and found that removal of the first 41 amino acids of Aα chain (Aα 1–41) did not affect the assembly and secretion of dimeric fibrinogen 14.…”
Section: Discussionmentioning
confidence: 99%